Different concentration of human cord blood HMGB1 according to delivery and labour: A pilot study. (August 2018) - D'Angelo, G.; Marseglia, L.; Granese, R.; Di Benedetto, A.; Giacobbe, A.; Impellizzeri, P.; Alibrandi, A.; Ferro, E.; Palmara, A.; Manti, S.; Arrigo, T.; Salpietro, C.; et al.
Highlights: Many inflammatory mediators are involved from the beginning of pregnancy to the birth. HMGB1 plays a role in embryo implantation and in later events, as labour and delivery. This study evidences that HMGB1 could be involved in the mechanisms of birth. Our data could reveal an action of this alarmin related to mode of delivery and to the presence of labour. Abstract: Objective: Oxidative stress is involved in several maternal conditions characterized both by an increase in free radicals synthesis and a parallel decrease in the antioxidant activity. Parturition induces considerable oxidative stress and many inflammatory mediators, among which HMGB1, are involved from the beginning of pregnancy to the birth of the infant. We evaluated serum cord blood HMGB1 levels in a population of neonates to investigate correlation with mode of delivery, as well as the influence of labour. Setting and patients: The study subjects were 325 neonates delivered at University Hospital "G. Martino" of Messina over an 18-month period. Following cord separation, venous blood sampling was performed on umbelical cords. Results: In the cord venous blood, we found HMGB1 values significantly more elevated in spontaneous vaginal group when compared to elective or emergency caesarean section group. Regarding labour, umbilical cord venous blood HMGB1 levels were significantly higher in the spontaneous and induced labour group, compared to non-labouring women. Conclusion: These results could highlight a possible role of HMGB1 during birth time related to mode of delivery and labour.